ANALISIS KAPASITAS TAMPUNGAN BANJIR KOLAM LUMPUR SIDOARJO - Sutanto, Samuel J. (JURNAL SUMBER DAYA AIR, 2018)
A simulation using the HEC-HMS model has been carried out to discover height of flood level in main pond. The result shows that existing condition of the pond is not sufficient for controlling flood although the pond had been dredged. Flood will overflow about 0.57-0.69m above the dyke in existing condition, and about 0.062-0.12m in dredged condition. Suggestions for prevention action are adding the amount of intake pipes, increasing dyke elevation and extending the dredging area. Flood will also occur in pond 5 particularly for the return period of 10 years if BPLS does not take serious action of prevention such as dredging and increasing dyke elevation.